كاریگه‌ری ئاووهه‌وا له‌سه‌ر ته‌ندروستی و حه‌وانه‌وه‌ی مرۆڤ له‌ پارێزگای سلێمانی 2004-2020 (توێژینەوەی هەڵێنجراو) - تالب, جه‌زا تۆفیق; مارف, شه‌ماڵ علی (Sulaimani Journal for Humanities, 2023)
Weather is considered as one of the most important natural environmental elements, which have effect of human health and comfort, Also the type of activists according to the weather will change the area that visited. The type of human feeling in an open environment is created as an interaction between many weather elements such as solar radiation, temperature, humidity, winds, and precipitation. From this point of perspective, applied climate researchers have put many standards on the type of human feeling under the use of climate elements. This research under the title (The effect of climate on human comfort and health) is an attempt to introduce tourism climate in Sulaymaniyah governorate by considering the differences between places and times.